A história ensinada em Ipuã em dois tempos : 1960 e 2000 - Silva, Renata Fernandes e (2007)
This work has the purpose of knowing the proccess by which the History teaching has been employed in Brazil, mainly in the city of Ipuã, São Paulo, in the period between the decades of 1960 and 2000. For that, we utilize as sources the legislation of the period, school curriculum proposals, the curriculum programs elaborated by the teachers and the teaching materials used throughout the period in study. We have divided our work in three parts, being the first a bibliographical study by means of a revision of the pertinent literature, the direction of History teaching in Brazil, seeking to understand it since before its constitution as school subject occurred in the Imperial period up to the decade of 2000. In the second part we reflect on the history of the city of Ipuã, approaching its history, the educational matter in the municipality and the history of the analyzed school, that is, its particularities in reference to the national scope. And in the last part, we carry out a comparative analysis of the curriculum proposals and the sources collected presenting the changes in the teaching of History as subject in the decades in study, observing its different objectives throughout the decades. From this study, we confirm the propositions of Chervel as regards the objectives of the school subjects because we understand that these latter change according to the proposed aims and that the contents of the school subjects which are taught are imposed to the school by the society and the culture that surround it, having the school a central role, the contents to be taught and the pedagogical methods applied are chosen, most of the time, influenced by determined purposes, that can be of cultural, psychological, politico-social, religious order, etc.